P110δ is required for innate immunity to transplantable lymphomas. (20th March 2007) - Saudemont, A.; Okkenhaug, K.; Colucci, F.
Abstract : NK cell (natural killer cells) are lymphocytes of innate immunity that kill tumour cells and respond to infections, without prior stimulation. A balance of activating and inhibitory signals regulates NK cell cytotoxicity, but the molecular mechanisms are not fully understood. General inhibitors of PI3K (phosphoinositide 3-kinase) suppress cytotoxicity in human and mouse NK cells. However, which isoforms and how they regulate NK cell activation is unknown, and no data have been published on mice carrying PI3K mutations. p110δ expression is restricted to leucocytes, where it plays central roles in lymphocyte development and signalling. We have used mice carrying a catalytically inactive mutant form of p110δ in order to determine its role in NK cell biology. We show here that p110δ is not required to kill tumour cells, but unexpectedly p110δ mutant mice failed to fully reject transplanted lymphomas. Our results show for the first time a critical role for p110δ in NK cell biology in vivo .